Internal-Notched Flexure Test for Measurement of Mode II Delamination Resistance of Fibre-Reinforced Polymers. (10th December 2013) - Fan, Chengye; Jar, P.-Y. Ben; Cheng, J.-J. Roger
Abstract : This paper introduces a new test, method, named internal-notched flexure (INF) test, that is designed to measure the critical energy release rate of fibre-reinforced polymers for delamination growth in shear mode (mode II). The INF test generates stable delamination growth, with a monotonic increase of load and displacement in a nearly linear fashion. Values of the mode II delamination toughness were deduced using experimental compliance fitting method. Good repeatability of the results was obtained. Compared with the end-notched flexure (ENF) test using the same material, the INF test yielded higher delamination resistance, possibly due to the bridging fibres found between fracture surfaces of the INF test specimens.